2021
DOI: 10.1590/1808-057x202009230
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between earnings management and abnormal book-tax differences in Brazil

Abstract: The aim of this study was to verify whether the discretionary actions of managers to manage earnings can be captured by abnormal book-tax differences (ABTD). In Brazil, there are no studies with the disaggregated use of earnings management (EM) through operational choices as a proxy for discretionary decisions to be captured by ABTD. Moreover, the previous studies focus on the period before the International Financial Reporting Standards (IFRS) were required in Brazil or when they were still being implemented,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 45 publications
2
3
0
Order By: Relevance
“…This implies that companies implementing AEM practices tend to engage in higher levels of tax avoidance. These results are consistent with previous studies conducted by Frank et al (2009), Ginting & Martani (2017), Surahman & Firmansyah (2017), Morais &Macedo (2021), andMasri (2022). Moving on to REM, as shown in Tables 5 and 7, different REM methods shows varying results.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…This implies that companies implementing AEM practices tend to engage in higher levels of tax avoidance. These results are consistent with previous studies conducted by Frank et al (2009), Ginting & Martani (2017), Surahman & Firmansyah (2017), Morais &Macedo (2021), andMasri (2022). Moving on to REM, as shown in Tables 5 and 7, different REM methods shows varying results.…”
Section: Discussionsupporting
confidence: 92%
“…On the other hand, REM_EXP (Real Earnings Management through Discretionary Expenses) is negatively related to ABTD, suggesting that companies employing discretionary expenses for earnings management tend to have lower levels of tax avoidance. The negative relationship between REM_EXP and ABTD findings align with previous studies by Geraldina (2013), Morais &Macedo (2021), andMasri (2022).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…These differences between book and taxable income are called book-tax differences (BTDs) in the literature. Morais and Macedo (2021) recently showed that, in Brazil, the BTD captures the discretionary actions of managers related to earnings management via accounting decisions.…”
Section: Introductionmentioning
confidence: 99%